2014
DOI: 10.1111/ped.12466
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and glomerular hypertrophy in extremely low‐birthweight children

Abstract: Reduced number of glomeruli associated with prematurity was speculated to have caused compensatory glomerular hyperfiltration, hypertrophy, and hypertension in children born with ELBW when they developed proteinuria. ARB could have been effective for proteinuria by reducing glomerular hypertension. Physicians should be aware of proteinuria in children born with ELBW because there is an increasing number of ELBW survivors as a result of advances in medical technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…There is increasing evidence that some children with LBW already have decreased renal function. We reported some LBW infants who showed proteinuria and glomerular hypertrophy from childhood . Frankfurt et al .…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…There is increasing evidence that some children with LBW already have decreased renal function. We reported some LBW infants who showed proteinuria and glomerular hypertrophy from childhood . Frankfurt et al .…”
mentioning
confidence: 73%
“…We reported some LBW infants who showed proteinuria and glomerular hypertrophy from childhood. 8 Frankfurt et al showed that infants with lower birthweight and gestational age had a reduced estimated GFR (eGFR) based on cystatin C (CysC) levels (CysC-eGFR) at 3 years of age. 9 Furthermore, not all LBW infants develop CKD, and certain prognostic factors are likely to affect the onset of CKD.…”
mentioning
confidence: 99%
“…Renal biopsy showed a diffuse increase in glomerular size, consistent with glomerular hypertrophy. The authors speculated that there was compensatory glomerular hyperfiltration, hypertrophy and hypertension in children born with extremely low birthweight when they developed proteinuria . Observational studies have also revealed high rates of CKD in survivors of neonatal acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…This form of hypertrophy could have arisen from considerable changes in efferent and afferent flows/pressures exerted on acellular glomeruli 43 . Excessive filtration and proteinuria could have also contributed to the condition 44 . Cellular debris and vascular cast formation in the Bowman's space that could have arisen from ischemia-derived blood cell apoptosis or necrosis observed in chronic diseases are also likely contributing factors 45 .…”
Section: Severe Dextran Extravasation and Alterations To Capillary Blood Flow Observed Across One Week Of Transplantationmentioning
confidence: 99%